(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The purpose of the author is to define the theoretical and economic essence of "financing of joint-stock companies through stocks." In the author’s opinion, first of all, it is impossible to talk about financial indicators that reflect his position, without specifying "financing of joint-stock companies through stocks." Based on the results of the study, the author’s definition was formulated for the concept of "financing joint-stock companies through stocks". The author provides a description of the financing of joint-stock companies, based on the strategic goals of joint-stock companies and sources of funding. Scientific conclusions on the topic were also made.